Associations of Symptomatic Knee Osteoarthritis With Histopathologic Features in Subchondral Bone. Issue 6 (2nd May 2019) - Aso, Koji; Shahtaheri, S. Mohsen; Hill, Roger; Wilson, Deborah; McWilliams, Daniel F.; Walsh, David A.
Abstract : Objective: Subchondral bone and the osteochondral junction are thought to contribute to osteoarthritis (OA) knee pain. We undertook this study to identify osteochondral pathologies specifically associated with symptomatic human knee OA. Methods: Medial tibial plateau samples from 2 groups of subjects (n = 31 per group) were matched for macroscopic chondropathy scores. The symptomatic chondropathy group had undergone total knee replacement for OA knee pain, at which time specimens of the medial tibial plateau were obtained. The asymptomatic chondropathy group included subjects who died of unrelated illness (specimens were obtained at postmortem examination) and who had not previously sought help for knee pain. OA histopathology, immunoreactivity for nerve growth factor (NGF) and CD68 (macrophages), tartrate‐resistant acid phosphatase–positive subchondral osteoclasts, and synovitis were compared between groups. Results: Mankin scores, subchondral bone density, and subchondral CD68‐immunoreactive macrophage infiltration were similar between the 2 groups. NGF‐like immunoreactivity was found in subchondral mononuclear cells and osteoclasts, as well as in chondrocytes. NGF in osteochondral channels and osteoclast densities in subchondral bone were higher in the symptomatic chondropathy group than in the asymptomatic chondropathy group ( P < 0.01 and P = 0.02, respectively), as were synovitis scores ( P < 0.01). Osteochondral pathology was not significantly associated with synovitis score. The differences in NGF expression and in osteoclast density remained significant after adjustment for age and synovitis score ( P = 0.01 and P = 0.04, respectively). Osteochondral NGF and osteoclast densities, together with synovitis scores, explained 28% of sample allocation to symptomatic or asymptomatic groups. Conclusion: Subchondral pathology was associated with symptomatic knee OA, independent of chondropathy and synovitis. Increased NGF expression in osteochondral channels and increased osteoclast density appear to be key features associated with bone pain in knee OA.